The Path of the Ocean Traditional Poetry of Polynesia - Sinclair, Marjorie (University of Hawai'i Press, 1982)
The Path of the Ocean is the first anthology of representative Polynesian poetry to be offered as a book of poetry rather than as a ethnological or historical document. Guided primarily by literary taste, Marjorie Sinclair has gathered poems from many sources and from translations with many kinds of expertise. She has scrupulously edited the old translations, modernized where necessary, and in some cases has translated or adapted the poetry. The arrangement of the anthology is rough geographic. It begins with Hawaii and travels southward, sometimes to the east and sometimes to the west until finally New Zealand is reached. As the title suggests, a journey that conveys scope, complexity, and deep humanity of the poetic spirit of the Polynesians.